PEMBUATAN ALAT PENDETEKSI KEBISINGAN UNTUK BUDIDAYA BURUNG LOVE BIRD BERBASIS ARDUINO DAN ANDROID MELALUI WIFI - Akhmad Baihari Salat (Universitas Wahid Hasyim, 2019)
Created a tool to increase Love Bird production so that farmers do not have to worry about the condition of the Love Bird bird if there is noise that will disrupt the bird while laying eggs.This research was conducted by making a detection device to provide information on the status of noise intensity through Android.Thus it can prevent the Love Bird from being stressed when incubating its eggs, the effect is that if the Love Bird sires are disturbed by sound, they will lay eggs outside their cages